Walking recovers cartilage compressive strain in vivo - Shu-Jin Kust; Kyle D. Meadows; Dana Voinier; JiYeon A. Hong; Dawn M. Elliott; Daniel K. White; Axel C. Moore (Osteoarthritis and Cartilage Open)
Background: Articular cartilage is a fiber reinforced hydrated solid that serves a largely mechanical role of supporting load and enabling low friction joint articulation. Daily activities that load cartilage, lead to fluid exudation and compressive axial strain. To date, the only mechanism shown to recover this cartilage strain in vivo is unloading (e.g., lying supine). Based on recent work in cartilage explants, we hypothesized that loaded joint activity (walking) would also be capable of strain recovery in cartilage. Methods: Eight asymptomatic young adults performed a fixed series of tasks, each of which was followed by magnetic resonance imaging to track changes in their knee cartilage thickness. The order of tasks was as follows: 1) stand for 30 ​min, 2) walk for 10 ​min, 3) stand for 30 ​min, and 4) lie supine for 50 ​min. The change in cartilage thickness was used to compute the axial cartilage strain. Results: Standing produced an average axial strain of −5.1 ​% (compressive) in the tibiofemoral knee cartilage, while lying supine led to strain recovery. In agreement with our hypothesis, walking also led to cartilage strain recovery. Interestingly, the recovery rate during walking (0.19 ​% strain/min) was nearly 3-fold faster than lying supine (0.07 ​% strain/min). Conclusions: This study represents the first in vivo demonstration that joint activity is capable of recovering compressive strain in cartilage. These findings indicate that joint activities such as walking may play a key role in maintaining and recovering cartilage strain, with implications for maintaining cartilage health and preventing or delaying cartilage degeneration.